Implementasi Pendampingan Keluarga Balita Stunting dengan Metode One Team One Family Menuju Desa Berdaya - Rina Sri Widayati; Ita Permatahati; Nur Amalina; Suratman Suratman; Sintha Harlina Putri; Meidiana Nurul Aisyah (Universitas Muhammadiyah Surakarta, 2024)
Stunting is a growth disorder in children under five years old caused by chronic malnutrition and recurrent infections. This condition is characterized by stunted growth in height in children under five years of age due to long-term malnutrition. The problems identified in Sanggrahan Village are related to health problems due to a lack of understanding about nutrition, family health, knowledge, environment, attitudes and behavior regarding stunting which is still a priority program. 18 children under five with stunted growth were found in Sanggrahan Village. This research aims to implement the One Team One Family method in an effort to reduce the prevalence of stunting and build empowered villages. Through an individual approach, families of stunted toddlers receive intensive assistance in the fields of nutrition, health and childcare. The research results show that the one team one family method is effective in increasing family knowledge about stunting, improving nutrition for toddlers and encouraging children's growth and development. Apart from that, this assistance is expected to be able to empower families and communities in overcoming stunting in a sustainable manner.